2010
DOI: 10.1007/s00011-010-0200-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential dose effects of recombinant IL-25 on the development of dextran sulfate sodium-induced colitis

Abstract: ObjectiveWe evaluated different dose effects of rIL-25 on acute ulcerative colitis.Materials and methodsMice were fed 2.5% dextran sulfate sodium (DSS) for 5 days while infused i.p. with repeated doses of rIL-25 (0.2, 0.4 and 0.8 μg) in PBS or PBS only after every 24 h at the same time as the start of the DSS exposure. Clinical, macroscopical and microscopical assessment of colitis severity with survival study was performed. Colonic IL-25 expression and production of IFN-γ, IL-10 and IL-4 was also analyzed.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Histological evaluation of H&E-stained tissue sections of colon showed that IL-25 −/− mice treated with DSS had lower HAI with only mild inflammation, while extensive inflammation developed in DSS-treated WT mice based on the extent of focal crypt lesions, loss of goblet cells, and infiltration of inflammatory cells (Figure 1 D & E). These results suggest that endogenous IL-25 plays a pro-inflammatory role in DSS-induced acute colitis, rather than an anti-inflammatory role proposed by a previous study using exogenous IL-25 [ 19 , 20 ].
Figure 1 Mice genetically deficient in IL-25 are protected from acute dextran sulfate sodium (DSS)-induced colitis.
…”
Section: Resultsmentioning
confidence: 47%
See 3 more Smart Citations
“…Histological evaluation of H&E-stained tissue sections of colon showed that IL-25 −/− mice treated with DSS had lower HAI with only mild inflammation, while extensive inflammation developed in DSS-treated WT mice based on the extent of focal crypt lesions, loss of goblet cells, and infiltration of inflammatory cells (Figure 1 D & E). These results suggest that endogenous IL-25 plays a pro-inflammatory role in DSS-induced acute colitis, rather than an anti-inflammatory role proposed by a previous study using exogenous IL-25 [ 19 , 20 ].
Figure 1 Mice genetically deficient in IL-25 are protected from acute dextran sulfate sodium (DSS)-induced colitis.
…”
Section: Resultsmentioning
confidence: 47%
“…Our results are contrary to a previous study showing that exogenous IL-25 had an inhibitory effect on the development of DSS colitis [ 19 ]. The reason for the inconsistency is not known, but a follow-up study from the same group indicated that only high doses (0.8 μg daily) of exogenous IL-25 protected, while low doses (0.2 μg daily) of IL-25 aggravated the DSS-induced colitis [ 20 ]. We made attempts to replicate those studies with exogenous IL-25 [ 19 , 20 ], but the results were inconclusive since daily IL-25 administration significantly reduced water/DSS consumption of the mice, which altered the outcome (Zhao A, et al unpublished results).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mchenga et al . found that, in dextran sulfate sodium-induced colitis, low dose (0.2 mg) aggravated, while high dose (0.8 mg) significantly attenuated colitis22. This phenomenon was also observed on Granulocyte macrophage colony stimulating factor (GM-CSF).…”
Section: Discussionmentioning
confidence: 89%